Mathematical Methods for Robust and Nonlinear Control EPSRC Summer School - Turner, Matthew C.; Bates, Declan G. (Lecture Notes in Control and Information Sciences, 2007)
The underlying theory on which much modern robust and nonlinear control is based can often be dif?cult for the student to grasp. In particular, the mathematical - pects can be problematic for students from a standard engineering background. The EPSRC sponsored Summer School which was held in Leicester in September 2006 attempted to "?ll the gap" in students' appreciation the theory relevant to several important areas of control. This book is a collection of lecture notes which were p- sented at that workshop and consists of, broadly, two parts. The ?rst nine chapters are devoted to the theory behind several areas of robust and nonlinear control and are aimed at introducing fundamental concepts to the reader. The last six chapters contain detailed case studies which aim to demonstrate the use and effectiveness of these modern techniques in real engineering applications. It is hoped that this book will provide a useful introduction to many of the more common robust and nonlinear control techniques and serve as a valuable reference for the more adept practitioner. Leicester, Matthew C. Turner May 2007 Declan G. Bates Contents List of Contributors . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . XV Part I Theory of Robust and Nonlinear Control 1H Control Design ? Declan G. Bates . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 3 1. 1 Introduction . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 3 1. 2 Design Speci?cations and Fundamental Trade-offs . . . . . . . . . . . . . . . . . . 5 1. 2. 1 Linear Design Speci?cations for Robust Control Systems . . . . . 6 1. 2. 2 Frequency Domain Design Speci?cations and Fundamental Trade-offs . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 6 1. 3 Mixed-sensitivityH Controller Design . . . . . . . . . . . . . . . . . . . . . . . . . .